Clinical protocols for adults with acute abdominal pain in Australian emergency departments. Issue 3 (4th February 2019) - Chong, Vivienne; Schultz, Timothy J.; Donnelly, Frank
Abstract: Rationale, Aims and Objectives: Patients with acute abdominal pain are a common presentation in hospital emergency departments; however, international studies have demonstrated that hospitals often lack clinical protocols to guide care. This study aimed to investigate whether Australian hospital emergency departments have acute abdominal pain clinical protocols, identify hospital‐level predictors of the presence of these clinical protocols, and assess the quality of protocols. Methods: A survey was sent to all Australian hospitals with emergency departments, collecting data on hospital characteristics and the presence of acute abdominal pain clinical protocols. Participating hospitals (n = 73, 26% response rate) were also asked to provide a copy of these protocols. The quality of these protocols was assessed using Appraisal of Guidelines for REsearch & Evaluation (AGREE) II. Results: Slightly more than half (n = 40) of the hospitals surveyed had acute abdominal pain clinical protocols, while 16 had a general pain protocol. In binomial logistic regression, two independent variables were related to the presence of a protocol, geographic region ( P = 0.008) and advanced practice nurses/nurse practitioners' presence on staff ( P = 0.024). The mean score for the overall quality assessment of these protocols was 4.2 on a seven‐point Likert scale; in terms of the six domains of quality, "Clarity of presentation" and "Scope and purpose" were highest. The overall quality of clinical protocols increased with remoteness, χ 2 (3) = 8.341, P = 0.039, and was lower in hospitals with medical staff on site (U = 2.5, P = 0.007). Conclusion: There is a documented standard for pain management of acute abdominal pain in about three quarters of participating Australian emergency departments. The use and quality of clinical protocols is influenced by the physical location of hospitals and staff and skill mix of clinicians.